Implikasi Prinsip Persamaan pada Pokoknya sebagai Indikator Itikad Tidak Baik (Bad Faith) pada Sengketa Merek Daimaru Vs Diamaru (Studi Kasus Putusan Perkara Nomor: 623K/Pdt.Sus-HKI/2024) - Erfan, Errik; Kemala, Ratih (PT Elaborium Elevasi Indonesia, 2025)
The similarity in essence between one trademark and another that previously registered trademark can be an indicator that a registered trademark is based on bad faith when registering at the Directorate General of Intellectual Property Rights, as regulated in Article 21 Paragraph (3) of Law Number 20 of 2016 Concerning Trademarks and Geographical Indications. A trademark applicant with bad faith are also the reason for a trademark cancellation lawsuit in the Commercial Court. The purpose of this research is to understand how the implications of the principle of equivalence can serve as an indicator of bad faith in the registration of a trademark. This research uses a normative juridical approach by library research. From the research conducted, it was found that there is a diversity of views, especially among judges, regarding the terminology of bad faith. This is because there is no definitive description or definition of bad faith is not clearly explained in trademark law, namely the interpretation of Article 21 paragraph (3) of Law Number 20 year 2016. Based on this research, the principle of similarity essentially indicates that a trademark can be a sign of bad faith in the application for trademark registration because the similarity essentially refers to riding on the reputation of a. Previously registered trademark Keywords: Trademark. Substantial Similarity, Bad Faith